EQAWI: An E-Book for Qawāʿid al-Lughah al-ʿArabiyyah Al-Ibtidāiyyah Based on Student-Centered Learning - Moh Fauzan; Moch Wahib Dariyadi; Moh. Fery Fauzi; Said Ardif (LISANIA: Journal of Arabic Education and Literature, 2026)
This study aims to develop an Electronic Book Qawāʿid al-Lughah al-ʿArabiyyah (EQAWI) based on Student-Centered Learning (SCL) and to evaluate its feasibility. The developed EQAWI was tested on students of the Department of Arabic Literature, State University of Malang (DSA UM). Development comprises five steps: analysis, planning, development, evaluation, and revision. To determine the feasibility of EQAWI, the product was validated by material experts, media specialists, and lecturers of the Qawāʿid al-Lughah al-ʿArabiyyah Al-Ibtidāiyyah course at DSA UM. The final product, an Electronic Book (e-book), consists of 28 chapters, including cover pages, remarks by the head of DSA UM, introduction, table of contents, the main texts, references, and the author’s curriculum vitae. The EQAWI e-book was designed to support independent and interactive learning through the implementation of Student-Centered Learning principles. It also provides systematic and accessible materials that help students understand Arabic grammar more effectively. In addition, the use of digital media in EQAWI is expected to increase students’ motivation and participation in the learning process. Validation scores were consistently high: 98% from material experts, 96% from media experts, and 95% from the course instructor, indicating that the product is highly feasible. Students' trials involving 20 students yielded a score of 94.25%, which also indicates that the product is highly feasible. Overall, EQAWI achieved an average score of 95.81%, confirming that the product is highly feasible and does not require revision.